2003
DOI: 10.1002/aqc.552
|View full text |Cite
|
Sign up to set email alerts
|

Coral communities of Biscayne Bay, Florida and adjacent offshore areas: diversity, abundance, distribution, and environmental correlates

Abstract: ABSTRACT1. Hardbottom habitats of Biscayne Bay, a shallow lagoon adjacent to the city of Miami, Florida, USA, contain a limited number of coral species that represent a small subset of the species found at nearby offshore hardbottom and reef habitats of the Florida Reef Tract. Although the physical characteristics of this basin make it a marginal environment for coral growth, the presence of dense populations of Siderastrea radians and Porites furcata indicate that these, as well as other corals that are found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 32 publications
2
45
1
Order By: Relevance
“…Previous work has associated groundwater discharge with the distribution of epibenthic macrofauna over 100s of meters (Kohout & Kolipinski 1967), reduction of coral density and species richness (Lirman et al 2003), reduction of seagrass community diversity (Kamermans et al 2002), and a shift in dominant polychaete species over as little as 5 m (Zipperle & Reise 2005). Porewater salinity affects the distribution of harpacticoid copepods along with other environmental factors like sediment size, exposure, water saturation, and oxygen penetration (Moore 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has associated groundwater discharge with the distribution of epibenthic macrofauna over 100s of meters (Kohout & Kolipinski 1967), reduction of coral density and species richness (Lirman et al 2003), reduction of seagrass community diversity (Kamermans et al 2002), and a shift in dominant polychaete species over as little as 5 m (Zipperle & Reise 2005). Porewater salinity affects the distribution of harpacticoid copepods along with other environmental factors like sediment size, exposure, water saturation, and oxygen penetration (Moore 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Porites furcata, for example, is abundant in disturbed environments, which experience extreme fluctuations in temperature, sedimentation and salinity that exclude most other coral species (e.g. Biscayne Bay, Florida; Lirman et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with the literature on the sedimentation patterns in the near-shore littoral environments impacted by human activities. A study by Lirman et al [44] suggested that the sedimentation rates and specifically those measured near navigational inlets, are an order of magnitude higher than those found elsewhere. Grain size data indicate that the northern section of the study area is predominantly composed of various types of sand substrates whereas the mid-and southern sections have large sections of fine-grained sediments.…”
Section: Discussionmentioning
confidence: 85%
“…Also, they often occur over hard-bottoms which may become undistinguishable when fine grain sediment is layered over it. For example, Lirman et al [44] reported a chronic exposure of coral colonies in Biscayne Bay, FL, to sediment burial due to the impact of the extensive network of canals, levies and navigational inlets constructed in the study area over the past decades. Due to similarities in grain size [20] gravel and glacial seafloor material are considered identical for the purposes of this analysis.…”
Section: Seabed Suitability For Oce Deployment: a Conceptual Frameworkmentioning
confidence: 99%